Pengaruh Inflasi, Kurs, Pdb, Jumlah Uang Beredar, dan Bi Rate terhadap Indeks Saham Syariah Indonesia - Halisania, Pebriana Nur; Jafar, Mohamad Imannudin; Wahyuningsih, Desi; Azizah, Nur (Advances In Social Humanities Research, 2024)
The Indonesian Sharia Stock Index or can be abbreviated as ISSI is a sharia-based stock index which is officially registered on the Indonesian Stock Exchange (BEI) and the data is contained on the official website of the Financial Services Authority (OJK). This research aims to determine whether there is an influence of the variables Inflation (X1), Exchange Rate (X2), GDP (X3), Money Supply (X4), and BI Rate (X5) on the variable Indonesian Sharia Stock Index or ISSI (Y). Data from Inflation, Exchange Rates, GDP, Money Supply, and BI Rate are monthly data for the 2018-2022 period. The analytical method used is quantitative analysis using descriptive analysis methods, classical assumption tests, multiple regression analysis, F test (Simultaneous Test), t test (Partial Test) and coefficient of determination using SPSS version 25 software. From research using the t test It was found that the independent variables Exchange Rate, Money Supply, and BI Rate partially or individually had a significant effect on the dependent variable ISSI. Meanwhile, the independent variables Inflation and GDP partially or alone do not have a significant effect on the dependent variable ISSI. Then, with the F test simultaneously or together the independent variables Inflation, Exchange Rate, GDP, Money Supply and BI Rate have a significant effect on the dependent variable ISSI. The close relationship between the independent variable and the dependent variable is in the medium category with a contribution of 65.2%, while the remaining 44.8% is influenced by other variables which are not in the research.